The Bad Guys in attack of the zittens - Blabey, Aaron (New York, NY : Scholastic Inc., 2017)
"It's a zombie kitten apocalypse! Can the Bad Guys save the world from evil Dr. Marmalade's meowing monsters?!? They'll need help from foxy Agent Fox, a swampy secret zombie antidote, and the feistiest, toothiest, hungriest granny around. Get ready to watch the fur fly!"--OCLC.
2.5
3-6
3-6
Keywords: Animals -- Comic books, strips, etc. -- Juvenile fiction; Heroes -- Comic books, strips, etc. -- Juvenile fiction; Kittens -- Comic books, strips, etc. -- Juvenile fiction; Rescues -- Comic books, strips, etc. -- Juvenile fiction; Animals -- Fiction; Heroes -- Fiction; Kittens -- Fiction; Rescues -- Fiction; Animals -- Comic books, strips, etc. -- Fiction; Heroes and heroines -- Comic books, strips, etc. -- Fiction; Kittens -- Comic books, strips, etc. -- Fiction; Rescue work -- Comic books, strips, etc. -- Fiction; Graphic novels; Humorous comics